One Pot Synthesis of Mg2Al(OH)6Cl·1.5H2O Layered Double Hydroxides: The Epoxide Route - Oestreicher, Víctor Santiago Jesús (2013)
Pure Mg2Al(OH)6Cl·1.5H2O layered double hydroxide (LDH) has been synthesized at room temperature by a one-pot method, homogeneously driven by chloride-assisted glycidol rupture (epoxide route). Well-defined nanoplatelet texture was achieved and the LDH crystallization mechanism discussed. Nanoplatelets self-assemble in the form of highly oriented films with excellent optical properties. LDH films exhibited stability toward detaching in aqueous solutions and allowed a fast anionic exchange preserving a high transparency.